An Open Source Environment for Cell Broadband Engine System Software. - Gschwind, Michael; Erb, David; Manning, Sid; Nutter, Mark (Computer (00189162), 2007)
The article discusses the development of the the Cell Broadband Engine, or Cell BE. New computer architectures are generally introduced following changes in technology. The Cell BE was developed for used in the Playstation 3 video game console and implements a chip multiprocessor with programmable cores to serve varying applications. Open source software was utilized to development an environment to explore the Cell BE's architecture. Cell applications use instruction streams for the power processor element (PPE) and synergistic processing element (SPE) cores. Data multibuffering hides memory access latency to the slow external memory. An application programming interface was created to manage SPE threads.